The use of ICT in Sexual Reproductive Health for learning: Prevention of teen pregnancy - Chavarría de Cocar, Laura Noemí (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
ICT (Information and Communication Technologies) are tools for information and knowledge that teenagers and young adults use to acquire learnings that allow to guide and improve the quality of life. With the aim to enhance the degree of knowledge, the methodology is developed in three phases: first phase, bibliographic review; second phase, setting-up the questionnaire (pre-test); third phase, development of the educational guide: “Let’s talk about sexuality”; subsequently, a postest was applied. From the data, a comparison by Student’s t-test of related samples is made and it is stated that the educational guide improved conceptual learning in sexual reproductive health.